Therapeutic capacity of logotherapy and existential analysis - Silvia Längle (Национальный психологический журнал, 2018)
Background. Victor Frankl developed two methods based on the fundamental (spiritual) ability to self-distraction and self-transcendence, i.e. paradoxical intention and dereflection. Further development and extension of the concepts Person and Existence in the framework of existential analysis by Alfried Längle allowed to expand the scientific basis for the creation of new therapeutic interventions and their methodological description. It seems very relevant to present in the paper the analysis of the logotherapeutic and existential analytical psychotherapeutic methods that exist at the present moment. The Objective of this paper is to give an overview of the logotherapy methods (LT) and existential analysis (EA), and to try and explain why they work. Also the author tries to clarify the logic of existential -analytical methods in correlation with EA anthropology and methodology. Design. The review of the LT and EA methods is presented here as they are currently used in psychotherapeutic practice and are taught as part of the training program on psychotherapy and counseling of the International Society for Logotherapy and Existential Analysis (GLE-International). The explanation of how the methods of logotherapy and existential analysis operate are done by correlating the EA methods in the first part of the paper with its anthropological concept, and in the second part – with the level (or extension) of the disturbance influenced by the method used and the psychotherapeutic work accordingly. Results. Three different levels or layers of LT and EA methods distinguished from each other by the principles of psychotherapeutic work are characterized. The first two levels are the area of action of short-term therapy including counseling on the one hand, and process-oriented therapeutic procedures, on the other hand. The third level developing the process of developing a personal dialogue is aimed at the Person concept. Being the nucleus of EA, Personal Existential Analysis (PEA) is considered to be an intra- or interpersonal dialogical process through which a person claims himself/herself through a decisive occupation of a position, being faced with a certain situation. The therapeutic method of PEA (introductory part, 3 steps including all stages) is described. Conclusion. The methods described provide the therapist with an array of various interventions aimed at activating the patient. Interventions are designed to help the patient find themselves in an existential relationship, gain their own voice, give their strength, help them find a description and give expression to new, better ways of being.